Revisiting "New Cambridge": The three financial balances in a general stock-flow consistent applied modeling strategy - Claudio H. dos Santos; Antonio C. Macedo e Silva (Levy Economics Institute of Bard College, 2010)
This paper argues that modified versions of the so-called 'New Cambridge' approach to macroeconomic modeling are both quite useful for modeling real capitalist economies in historical time and perfectly compatible with the 'vision' underlying modern Post-Keynesian stock-flow consistent macroeconomic models. As such, New Cambridge-type models appear to us as an important contribution to the tool kit available to applied macroeconomists in general and to heterodox applied macroeconomists in particular.
Keywords: B50; C82; E12; 330; stock-flow vonsistent models; New Cambridge; aggregate financial balances; heterodox applied macroeconomics